Analysis of Factors that Influenced Burnout Occurence during the Enforcement of Area Restriction Policy among Employees in BNN Rehabilitation Center - Palupi Lindiasari Samputra; Agrippina Decilia Putri (Faculty of Economics and Business Udayana University, 2021)
This study aimed to analyze the factors that influence employee behavior due to limited land at the BNN Rehabilitation Center, with a quantitative approach using factor analysis methods. The research sample was the staff of the BNN Rehabilitation Center, totaling 106 respondents. Data collection used a questionnaire based on the MBI (Maslach Burnout Syndrome Inventory). This study indicates that four factors cause employee burnout, namely work environment, coworker support, work concept, and self. The forms of burnout from BNN employees include; decreased achievement, emotional, and conflict with coworkers.